Effective implementation of change into routine work. Thinking over ways and means of a learning experience in Cardiology - Angelino, Elisabetta (Monaldi Archives for Chest Disease, 2015)
Effective implementation of change in patientsâ€™ care is a substantive problem. Organizational learning is viewed as process of seeking, selecting, and adapting new â€œroutinesâ€ to improve performance but learning from experience is not automatic, but rather may result from action and reflection within the organization. Keywords: hospital discharge, intervention development, learning, checklist.